NOVELS AND MOVIES IN EFL CLASSROOM - Sari, Ayu Paramita (Universitas Borneo Tarakan, 2019)
Teaching English is a challenge for EFL teachers. It has become more complex and difficult due to the development of new technology. In order to help the learnersâ€™ mastery (increase the proficiency) of language skills, language teachers have to provide quality teaching materials that will be engaging, interesting, up-to-date while simultaneously being a tool that will ensure that the students learn. Â Moreover, the students sometimes feel bored and confused when the teacher teaches them using monotonous strategies or traditional strategies. Nowadays, one of them is by using Films and Novels to makes the students more interested in learning. Since these two genres of literature can attract students and help them to learn the benefits of English skills easily and eventualy the culture of embedded in the materials. Many schools and courses already use this as a facility and strategy to help teachers in teaching and to help students in comprehension or understanding English literature in learning process. According to statistics from the Kaiser Family Foundation (Rideout, Roberts Foehr, 2005), youth ages 8-18 spend approximately 6.5 hours each day using media, an activity that far surpasses the time they spend with parents, doing homework or playing sports. This paper aims to highlight the benefits of using novels and movies in (English Foriegn Language) EFL classrooms.